(untitled) (Journal of the College of Basic Education, 2022)
The art of debate is of central importance as far as rhetoric , literary heritage , prose and poetry are concerned . The root of this art can be traced since the Greek philosophy and due to translation , it became part of the Arabic culture ; a matter which added certain conditions that should be regarded and followed . Maqamat offered an environment of debates , discussions , going through rhetorical and expository means , and the employment of artistic and rhetorical tools ; starting from the first example of Maqamat ( Al- hamathani Maqamat ) throughout Al-Harriri ones . The sixty Maqamat by Ibn Mari ( 589H ) are considered to be a rich example of Maqamat that celebrate the art of debate . Ibn Mari had followed the style of both Al harriri and Hamathani ( by selecting a narrator to his Maqamat , wandering through different cities , and his manipulative attitude to gain money ) This research is dedicated to discuss the thirty four maqama ( which is called the Ma’ari Maqama ) which is based on a debate between an elderly man ( Sheikh) who praises the virtues of Ramadan and a teenager who praises Shawal at a judge’s council ; a debate that ends with the old man ‘s winning . The research discusses the styles used in debates and the means of delivering the different opinions